Hypertension in stroke survivors and associations with national premature stroke mortality: data for 2·5 million participants from multinational screening campaigns. Issue 8 (August 2022) - Lin, Queran; Ye, Tingxi; Ye, Pengpeng; Borghi, Claudio; Cro, Suzie; Damasceno, Albertino; Khan, Nadia; Nilsson, Peter M; Prabhakaran, Dorairaj; Ramirez, Agustin; Schlaich, Markus P; Schutte, Aletta E; et al.
Summary: Background: Blood pressure control has a pivotal role in reducing the incidence and recurrence of stroke. May Measurement Month (MMM), which was initiated in 2017 by the International Society of Hypertension, is the largest global blood pressure screening campaign. We aim to compare MMM participants with and without a previous history of stroke and to investigate associations between national-level estimates of blood pressure management from MMM and premature stroke mortality. Methods: In this annual, global, cross-sectional survey, more than 2·5 million volunteers (≥18 years) from 92 countries were screened in May, 2017, and May, 2018. Three seated blood pressure readings and demographic, lifestyle, and cardiovascular disease data were collected. Associations between risk factors and stroke history were analysed with mixed-effects logistic regression, and associations between national-level estimates of blood pressure management and premature stroke mortality based on Global Burden of Disease data were investigated with linear regression. Findings: 2 222 399 (88·4%) of 2 515 365 participants had recorded data on a history of stroke, of whom 62 639 (2·8%) reported a previous stroke. Participants with a history of stroke had higher rates of hypertension (77·0% vs 32·9%, p<0·0001) and of treated (90·2% vs 57·0%, p<0·0001) and controlled (55·9% vs 32·4%, p<0·0001) hypertension than those without a history of stroke. A third of participants with a history of stroke had either untreated hypertension or treated but uncontrolled hypertension (blood pressure ≥140/90 mm Hg). Strong positive associations were found between national premature stroke mortality and mean systolic blood pressure (84·3 [95% CI 38·8 to 129·9] years of life lost [YLL] per 100 000 people per mm Hg increase) and the percentage of participants with raised blood pressure (49·1 [22·6 to 75·6] YLL per 100 000 people per 1% increase). Strong negative associations were found between national premature stroke mortality and the percentage of participants with hypertension on treatment (−21·0 [−33·0 to −8·9] YLL per 100 000 people per 1% increase) and with controlled blood pressure (−31·6 [−43·8 to −19·4] YLL per 100 000 people per 1% increase). Interpretation: Blood pressure control remains suboptimal worldwide among people with a history of stroke. National estimates of blood pressure management reflect national premature stroke mortality sufficiently to prompt policy makers to promote blood pressure screening and management. Funding: International Society of Hypertension and Servier Pharmaceuticals.